A validation study of three early warning scores in early identification of gastric cancer patients with deteriorating condition after gastrectomy - Xinli Shi; Huijuan Jie; Naifa Li; Qiongshan Liu; Yue Wang; Changquan Wu; Wenwen Jiang; Bolin Zhang; Shurong Lai; Honglu Xu (BMC Gastroenterology)
Abstract Objectives Early warning scores (EWS) aim to rapidly identify patients at risk of critical illness or life-threatening events before deterioration occurs in clinical settings. This study aims to validate the ability of three commonly used early warning scores, namely the National Early Warning Score (NEWS), the Early Warning Score (SEWS), and the Modified Early Warning Score (MEWS), to identify patients with deterioration after gastric cancer resection in general wards. Methods This retrospective case-control study included 110 patients who experienced clinical deterioration after gastrectomy for gastric cancer as case group, and 745 patients without deterioration as control group from a tertiary hospital in Guangdong Province, China. The discriminating ability (receiver operating characteristic curves), calibration (goodness-of-fit test) and net benefit (clinical decision curves) of the three EWS (NEWS, SEWS, MEWS) were explored to compare their early warning performance for patients at risk of post-operative deterioration. Results MEWS (goodness-of-fit p = 0.123 > 0.05) and SEWS (goodness-of-fit p = 0.235 > 0.05) both demonstrate good calibration and good discrimination ability (AUC 0.710, 95% CI 0.654–0.766;AUC 0.756, 95% CI 0.701–0.811). In contrast, NEWS not only has good calibration (goodness-of-fit p = 0.283 > 0.05) but also exhibits the best discrimination ability among the three scoring systems (AUC 0.835, 95% CI 0.785–0.884) and the highest net benefit. Conclusion Overall, NEWS may be more suitable for identifying gastric cancer patients at risk of post-operative clinical deterioration, as the early warning scoring model with best performance currently for post-gastrectomy observation.